Xianglian Pill ameliorates antibiotic-associated diarrhea by restoring intestinal microbiota and attenuating mucosal damage. (10th January 2021) - Yang, Lujia; Zhang, Qian; Huang, Jieyao; Liu, Danning; Lan, Yunfei; Yuan, Lujiang; Chen, Qianfeng
Abstract: Ethnopharmacological relevance: Xianglian Pill (XLP), a traditional Chinese pharmaceutical preparation for the treatment of gastrointestinal disease, possessing anti-inflammatory, anti-microbial and analgesic activities, may represent a promising candidate for the treatment of antibiotic-associated diarrhea (AAD). Aim of the study: This study aimed to unravel the underlying mechanism of XLP on the amelioration of AAD. Materials and methods: AAD was induced by intragastric administration of a mixture of cefuroxime and levofoxacin (300 mg/kg. bw + 200 mg/kg. bw) for five consecutive days. Then AAD mice were treated with XLP at the dose of 500, 1000 and 2000 mg/kg. bw, respectively for 5 days. The physical manifestations, diarrhea status were monitored during the drug delivery. Histopathology of colon, intestinal microbiota, inflammatory cytokines, tight junction protein and short chain fat acids (SCFAs) were determined. Results: Mice received cefuroxime and levofoxacin for 5 days developed medium to severe diarrhea. XLP treatment, however, mitigated the diarrhea status. Further evaluation revealed that XLP promoted the recovery of mucosa, maintained the integrity of tight junction, attenuated the inflammatory disorders, restored intestinal microbiota and increased SCFAs level in feces. Conclusion: XLP ameliorates AAD by restoring intestinal microbiota and attenuating mucosal damage. Graphical abstract: Image 1 Highlights: Xianglian Pill (XLP) was revealed to ameliorate antibiotic-associated diarrhea for the first time. XLP restored the intestinal microbiota. XLP increased the level of short-chain fatty acids and inhibited the production of inflammatory cytokines.